2017
DOI: 10.1016/j.eururo.2016.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide in Men with Chemotherapy-naïve Metastatic Castration-resistant Prostate Cancer: Extended Analysis of the Phase 3 PREVAIL Study

Abstract: Enzalutamide significantly improved radiographic progression-free survival (rPFS) and overall survival (OS) among men with chemotherapy-naïve metastatic castration-resistant prostate cancer at the prespecified interim analysis of PREVAIL, a phase 3, double-blind, randomized study. We evaluated the longer-term efficacy and safety of enzalutamide up to the prespecified number of deaths in the final analysis, which included an additional 20 mo of follow-up for investigator-assessed rPFS, 9 mo of follow-up for OS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
188
3
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(237 citation statements)
references
References 6 publications
5
188
3
19
Order By: Relevance
“…We observed a wide‐range of responses to these modalities, as also occurs in men with PC. Notably, results of studies using LuCaP PDXs identified AR amplification/activity as an important mechanism of resistance to ADT , supporting the use of enzalutamide (now FDA‐approved for men with mCRPC) , and also identified AR splice variants as an important mechanism of resistance to ADT which supported the development of new AR N‐terminal antagonists .…”
Section: Discussionmentioning
confidence: 89%
“…We observed a wide‐range of responses to these modalities, as also occurs in men with PC. Notably, results of studies using LuCaP PDXs identified AR amplification/activity as an important mechanism of resistance to ADT , supporting the use of enzalutamide (now FDA‐approved for men with mCRPC) , and also identified AR splice variants as an important mechanism of resistance to ADT which supported the development of new AR N‐terminal antagonists .…”
Section: Discussionmentioning
confidence: 89%
“…Androgen deprivation therapy, both surgical and biochemical castration, is the main treatment for relapsed patients and provides temporary relief to tumor burden; however, all patients will acquire lethal, castration-resistant prostate cancer (CRPC). Androgen receptor (AR)-targeted therapies for blocking the androgen signaling axis have improved, with more potent, second-generation antiandrogens such as enzalutamide, and 17-hydroxylase/17,20-lyase (CYP17) inhibitors, but these agents only increase median overall survival by approximately 4 months in chemotherapy-naïve patients (2, 3). …”
Section: Castration-resistant Prostate Cancermentioning
confidence: 99%
“…На сегодняшний день в рандомизированных исследованиях не проводилось прямого сравнения абиратерона и энзалутамида, одна-ко доступны результаты работ, в которых изучалось применение абиратерона в комбинации с преднизоло-ном (COU-AA-302) [8][9][10] и энзалутамида (PREVAIL) [11,12] по сравнению с плацебо у пациентов, ранее не получавших химиотерапии. Оба исследования яв-лялись рандомизированными двойными слепыми пла-цебоконтролируемыми, при этом различия в исходных характеристиках пациентов были минимальными.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…Однако при трактовке результатов необходимо учиты-вать разницу в подходах, которые применялись при формировании отчетов о нежелательных явлениях (НЯ). В исследовании PREVAIL отражались НЯ, про-явившиеся более чем у 10 % пациентов, и различия в частоте которых превышали 2 процентных пункта по сравнению с контрольной группой [11], в то время как в работе COU-AA-302 были отражены НЯ, часто-та возникновения которых превышала 15 % в хотя бы одной из групп [8]. Кроме того, даже в контрольных группах частота возникновения НЯ близка к 100 %, а частота возникновения НЯ III-IV степеней состав-ляет 37-44 %.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified